Extractive fermentation for the production and partitioning of lipase and citric acid by Yarrowia lipolytica. (November 2022) - Santos, Ariane Gaspar; Buarque, Filipe Smith; Ribeiro, Bernardo Dias; Coelho, Maria Alice Zarur
Abstract: Extractive fermentation is an efficient downstream process to segregate the desired product in a fermentative process. Here, an integrated extractive fermentation process with an aqueous two-phase system (ATPS) was applied to evaluate the lipase and citric acid production by Yarrowia lipolytica. For this purpose, the influences of polyethylene glycol (PEG) molecular weights, different salts and different concentrations as well as the pH of the potassium phosphate buffer were studied. Citric acid preferentially migrated to the salt-rich phase, whereas lipase mostly partitioned to the PEG-rich phase. The PEG2000 (30 wt%) + salt (7 wt%) system provided higher cell growth and citric acid production, whereas the PEG2000/Na2 SO4 ATPS showed a better recovery yield (79.75%) for citric acid. The increase in PEG molecular weight reduced lipase production and the partition coefficient (KL ). In the PEG 2000/KH2 PO4 -K2 HPO4 (pH 7) system, a lipase production of 634.32 U L −1 and KL = 2.22 was obtained. Lipase production kinetics in an Erlenmeyer (10 mL) and a bioreactor (1.5 L) demonstrated that in the ATPS, the fermentation medium caused a delay in the growth curve and a peak in lipase production, of which the latter allowed for a reduction in the dissolved oxygen concentration, limiting cell metabolism. Graphical Abstract: ga1 Highlights: Lipase and citric acid production by Y. lipolytica using extractive fermentation. Citric acid migrated preferentially to the salt-rich phase. Lipase partitioned mostly to the PEG-rich phase. PEG2000/KH2 PO4 -K2 HPO4 ATPS showed a lipase production of 634.32 U L −1 and KL = 2.22. The kinetics in the miniaturised system and bioreactor showed an extensive lag phase.